Women in white-collar work at the University of the Witwatersrand: a comparison between black and white female administrators - Mabapa, Rosina Moore (My University, 2017)
This research report seeks to explore the experiences of women in white-collar work, particularly by comparing the experiences of black and white female administrators at of the University of the Witwatersrand. What this report illustrates is that both race and generational differences play a significant role in informing the experiences of the female administrators. A qualitative methodology was used to collect data for this report, particularly in-depth interviews to get “detailed information” about the participants’ experiences, beliefs and thoughts. Three main generational groups have been identified among the Wits administrators: Baby Boomers, which is the older generation that is dominated by white female administrators; Generation X; and the Millennial group, which is dominated by black female administrators and consist of the younger generations. This research report thus argues that race has affected the workplace experiences of Wits administrators through generational differences. Furthermore, while generations share similar experiences and world views, they are not homogeneous categories
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters in Arts, Johannesburg, 2017
Keywords: Women white collar workers--South Africa; Women college administrators--South Africa; Generation X--Employment--South Africa; South Africa--Race relations